An optical multimode fiber as pseudothermal light source - Mehringer, Thomas; Oppel, Steffen; von Zanthier, Joachim (Applied Physics B-Lasers and Optics, 2017)
We report on a novel pseudothermal light source based on laser light coupled into an optical multimode fiber. The setup is simple, low cost, exhibits inherently high directional light emission and allows for a flexible arrangement. By measuring the photon statistics and spatial two point intensity correlations in the far field we show that the setup exhibits all characteristics of a Gaussian random sourc

Photon statistics as an interference phenomenon - Mehringer, Thomas; Mährlein, Simon; von Zanthier, Joachim; Agarwal, Girish (Optics Letters, 2018)
Interference of light fields, first postulated by Young, is one of the fundamental pillars of physics. Dirac extended this observation to the quantum world by stating that each photon interferes only with itself. A precondition for interference to occur is that no welcher-weg information labels the paths the photon takes; otherwise, the interference vanishes. This remains true, even if two-photon interference is considered, e.g., in the Hong-Ou-Mandel-experiment. Here, the two photons interfere only if they are indistinguishable, e.g., in frequency, momentum, polarization, and time. Less known is the fact that two-photon interference and photon indistinguishability also determine the photon statistics in the overlapping light fields of two independent sources. As a consequence, measuring the photon statistics in the far field of two independent sources reveals the degree of indistinguishability of the emitted photons. In this Letter, we prove this statement in theory using a quantum mechanical treatment. We also demonstrate the outcome experimentally with a simple setup consisting of two statistically independent thermal light sources with adjustable polarizations. We find that the photon statistics vary indeed as a function of the polarization settings, the latter determining the degree of welcher-weg information of the photons emanating from the two sources. (C) 2018 Optical Society of America.

Precision estimation of source dimensions from higher-order intensity correlations - Pearce, M. E.; Mehringer, Thomas; von Zanthier, Joachim; Kok, P. (Physical Review A, 2015)
An important topic of interest in imaging is the construction of protocols that are not diffraction limited. This can be achieved in a variety of ways, including classical superresolution techniques or quantum entanglement-based protocols. Here, we consider superresolving imaging in the far field using higher-order intensity correlations. We show that third-and fourth-order correlations can improve upon the first-and second-order correlations that are traditionally used in classical optics and Hanbury Brown-Twiss-type experiments. The improvement is achieved entirely by post-processing of the data. As a demonstrator, we simulate the far field intensity distribution of a circular aperture that emits thermal light and use maximum likelihood estimation to determine the radius of the aperture. We compare the achieved precision to the Cramer-Rao lower bound and find that the variance of measurements for the third-and fourth-order correlation functions are indeed closer to the Cramer-Rao bound than that of the second-order correlation function. The method presented here is general, and can be used for all kinds of incoherent emitters, geometries, and types of nois

Prime number decomposition using the Talbot effect - Pelka, Karl; Graf, Jasmin; Mehringer, Thomas; von Zanthier, Joachim (Optics Express, 2018)
We report on prime number decomposition by use of the Talbot effect, a well-known phenomenon in classical near field optics whose description is closely related to Gauss sums. The latter are a mathematical tool from number theory used to analyze the properties of prime numbers as well as to decompose composite numbers into their prime factors. We employ the well-established connection between the Talbot effect and Gauss sums to implement prime number decompositions with a novel approach, making use of the longitudinal intensity profile of the Talbot carpet. The new algorithm is experimentally verified and the limits of the approach are discussed. (C) 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement

Quantum imaging with incoherently scattered light from a free-electron laser - Schneider, Raimund; Mehringer, Thomas; Mercurio, Giuseppe; Wenthaus, Lukas; Classen, Anton; Brenner, Gunter; Gorobtsov, Oleg; Benz, Adrian; Bhatti, Daniel; Bocklage, Lars; Fischer, Birgit; Lazarev, Sergey; et al. (Nature Physics, 2018)
The advent of accelerator-driven free-electron lasers (FEL) has opened new avenues for high-resolution structure determination via diffraction methods that go far beyond conventional X-ray crystallography methods(1-10). These techniques rely on coherent scattering processes that require the maintenance of first-order coherence of the radiation field throughout the imaging procedure. Here we show that higher-order degrees of coherence, displayed in the intensity correlations of incoherently scattered X-rays from an FEL, can be used to image two-dimensional objects with a spatial resolution close to or even below the Abbe limit. This constitutes a new approach towards structure determination based on incoherent processes(11,12), including fluorescence emission or wavefront distortions, generally considered detrimental for imaging applications. Our method is an extension of the landmark intensity correlation measurements of Hanbury Brown and Twiss(13) to higher than second order, paving the way towards determination of structure and dynamics of matter in regimes where coherent imaging methods have intrinsic limitations(14).

Superresolving Imaging of Arbitrary One-Dimensional Arrays of Thermal Light Sources Using Multiphoton Interference - Classen, Anton; Waldmann, Felix; Giebel, Sebastian; Schneider, Raimund; Bhatti, Daniel; Mehringer, Thomas; von Zanthier, Joachim (Physical Review Letters, 2016)
We propose to use multiphoton interferences of photons emitted fromstatistically independent thermal light sources in combination with linear optical detection techniques to reconstruct, i.e., image, arbitrary source geometries in one dimension with subclassical resolution. The scheme is an extension of earlier work [S. Oppel et al., Phys. Rev. Lett. 109, 233603 (2012)], where N regularly spaced sources in one dimension were imaged by use of the Nth-order intensity correlation function. Here, we generalize the scheme to reconstruct any number of independent thermal light sources at arbitrary separations in one dimension, exploiting intensity correlation functions of order m >= 3. We present experimental results confirming the imaging protocol and provide a rigorous mathematical proof for the obtained subclassical resolutio